2015
DOI: 10.1002/lary.25601
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the maxillary sinus: A population‐based analysis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 44 publications
3
51
0
7
Order By: Relevance
“…Due to the relative rarity of MS‐SCC, no randomized prospective studies have been performed . Although Kim et al report a 13.5% risk of occult metastasis in patients who did not receive END at the time of primary resection, Dubal et al demonstrate that the risk could be as high as 22.2% in MS‐SCC, which would meet the criteria for the employment of END . Additionally, Le et al report a 20% 60‐month nodal relapse rate in patients without elective neck control versus 0% in patients with elective neck control via irradiation .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the relative rarity of MS‐SCC, no randomized prospective studies have been performed . Although Kim et al report a 13.5% risk of occult metastasis in patients who did not receive END at the time of primary resection, Dubal et al demonstrate that the risk could be as high as 22.2% in MS‐SCC, which would meet the criteria for the employment of END . Additionally, Le et al report a 20% 60‐month nodal relapse rate in patients without elective neck control versus 0% in patients with elective neck control via irradiation .…”
Section: Discussionmentioning
confidence: 99%
“…12 Although Kim et al report a 13.5% risk of occult metastasis in patients who did not receive END at the time of primary resection, Dubal et al demonstrate that the risk could be as high as 22.2% in MS-SCC, which would meet the criteria for the employment of END. 8,21 Additionally, Le et al report a 20% 60month nodal relapse rate in patients without elective neck control versus 0% in patients with elective neck control via irradiation. 22 In the first large randomized controlled clinical trial of END in cancers of the buccal mucosa, tongue, and floor of mouth, D'Cruz et al found an absolute overall survival benefit of 12.5 percentage points and a disease-free survival benefit of 23.6 percentage points in those who underwent an END over observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature from other countries, the survival rates of patients with carcinoma of the nasal cavity and paranasal sinus are not high, with 5-year survival rates of only 36.9-52% (4,12) and 5-year survival rates for patients with locally advanced disease of only 12-40% (13-15). Even with major surgery involving ocular evisceration with extensive range and damage, long-term survival rates are still as low as only 23-59% (13,(16)(17)(18). Fortunately, due to the intervention of chemotherapy, including ICT and CCRT, the 5-year OS of patients with squamous cell carcinoma of the nasal sinus has reached 59-76% in recent years (10,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%